Prevalence of retinopathy in prediabetes: protocol for a systematic review and meta-analysis. Issue 1 (7th January 2021) - Kirthi, Varo; Nderitu, Paul; Alam, Uazman; Evans, Jennifer; Nevitt, Sarah; Malik, Rayaz A; Jackson, Timothy L
Abstract : Introduction: There is growing evidence of a higher than expected prevalence of retinopathy in prediabetes. This paper presents the protocol of a systematic review and meta-analysis of retinopathy in prediabetes. The aim of the review is to estimate the prevalence of retinopathy in prediabetes and to summarise the current data. Methods and analysis: This protocol is developed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) guidelines. A comprehensive electronic bibliographic search will be conducted in MEDLINE, EMBASE, Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Google Scholar and the Cochrane Library. Eligible studies will report prevalence data for retinopathy on fundus photography in adults with prediabetes. No time restrictions will be placed on the date of publication. Screening for eligible studies and data extraction will be conducted by two reviewers independently, using predefined inclusion criteria and prepiloted data extraction forms. Disagreements between the reviewers will be resolved by discussion, and if required, a third (senior) reviewer will arbitrate. The primary outcome is the prevalence of any standard features of diabetic retinopathy (DR) on fundus photography, as per International Clinical Diabetic Retinopathy Severity Scale (ICDRSS) classification. Secondary outcomes are the prevalence of (1) any retinal microvascular abnormalities on fundus photography that are not standard features of DR as per ICDRSS classification and (2) any macular microvascular abnormalities on fundus photography, including but not limited to the presence of macular exudates, microaneurysms and haemorrhages. Risk of bias for included studies will be assessed using a validated risk of bias tool for prevalence studies. Pooled estimates for the prespecified outcomes of interest will be calculated using random effects meta-analytic techniques. Heterogeneity will be assessed using the I 2 statistic. Ethics and dissemination: Ethical approval is not required as this is a protocol for a systematic review and no primary data are to be collected. Findings will be disseminated through peer-reviewed publications and presentations at national and international meetings including Diabetes UK, European Association for the Study of Diabetes, American Diabetes Association and International Diabetes Federation conferences. PROSPERO registration number: CRD42020184820.